Case report of renal pelvis squamous cell carcinoma with tumor embolus in autosomal dominant polycystic kidney disease. Issue 33 (August 2016) - Xie, Jing; Zhang, Xue-bin; Wang, Wen-ze; Li, Han-zhong
Abstract: Introduction: Autosomal dominant polycystic kidney disease (ADPKD) is a multisystem hereditary disease characterized by formation of cysts in the ductal organs. Renal pelvis malignancy in ADPKD is very rare and sporadically reported in the previous literature. Here, we report the first case of renal pelvis squamous cell carcinoma with tumor embolus in a 35-year-old ADPKD patient. The patient presented with 3 months of persistent backache and intermittent fever, and was initially diagnosed as intracystic hemorrhage with inferior vena cava thrombosis formation. As a result, he received anticoagulation therapy in a local hospital. However, his backache got worsened during the therapy, and he lost 10 kg of his body weight from the onset of illness. In our hospital, computed tomography demonstrated a heterogeneous right renal mass as well as emboli in the inferior vena cava and bilateral renal veins. Positron emission tomography computed tomography and biopsy were also performed, but the results were equivocal. Considering the patient's willingness and the potential malignancy, we performed thoracoabdominal nephrectomy and embolectomy, and histological examination made the diagnosis of renal pelvis squamous cell carcinoma. After adjuvant chemotherapy including paclitaxel and carboplatin, the patient obtained improved physical status and was disease free at the 6-month follow-up. Although rare, renal pelvis squamous cell carcinoma should be considered in the differential diagnosis of renal mass in ADPKD patients. Conclusion: Our case suggested surgery combined with adjuvant chemotherapy might be effective treatments in such a condition.